Chemical Components of Agarwood (Aquilaria crassna) Essential Oils Grown in Various Regions of Asia - Kim Ngan, Tran Thi; Thu Thuy, Dinh Thi; Tuyen, Tran Thi; Inh, Cam Thi; Bich, Hoang Thi; Long, Pham Quoc; Chien, Nguyen Quyet; Kieu Linh, Huynh Thi; Yen Trung, Le Nguyen; Tung, Nguyen Quang; Nguyen, Duy Chinh; Bach, Long Giang; et al. (Asian Journal of Chemistry, 2019)
This study presents a chemometric study on agarwood (Aquilaria crassna) essential oils extracted from selected agarwood samples grown in various regions of Asia. Adopting gas chromatography-mass spectrometry (GC-MS) technique, it was revealed that essential oils, produced by hydrodistillation, constitutes mainly volatile aromatic compounds. Several major components are shared in all samples including dihydro-agarofuran-15-al, jinkoeremol, 10-epi-γ-eudesmol, agarospirol, valerianol, n-hexadecanoic acid, neopetasane and dihydrokaranone. Despite differences in composition, extraction yield and detected constituents found in analyzed samples, characteristic aromatic compounds were abundantly found in the Agarwood essential oil. These discrepancies could be due to cultivation season, climatic conditions and extraction methods. Unambiguous identification of components in agarwood essential oils thereby opens new potential in the application of high-value aromatic compounds in agarwood essential oil in cosmetic products, perfumes, and pharmaceuticals.